2010
DOI: 10.1093/cercor/bhq081
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Specific Noradrenergic Modulation of Inhibition in Cortical Layer II/III

Abstract: Norepinephrine (NE) is released in the neocortex after activation of the locus coeruleus of the brain stem in response to novel, salient, or fight-or-flight stimuli. The role of adrenergic modulation in sensory cortices is not completely understood. We investigated the possibility that NE modifies the balance of inhibition acting on 2 different γ-aminobutyric acid (GABA)ergic pathways. Using patch-clamp recordings, we found that the application of NE induces an α(1) adrenergic receptor-mediated decrease of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 69 publications
10
66
1
2
Order By: Relevance
“…Previous electrophysiological studies have emphasized the role of NA in the modulation of cortical glutamatergic neurotransmission (Nowicky et al, 1992, Dinh et al, 2009, the latter being the main determinant for the coupling between increased cortical activity and hemodynamic alterations (Attwell and Iadecola, 2002). This is consistent with the numerous c-Fos-positive pyramidal-shaped cells found in our study (not quantified) and, to a lesser extent, COX-2-immunopositive pyramids (ϳ20%).…”
Section: Mediators Of the Hemodynamic Responses To Lc Stimulation Glusupporting
confidence: 92%
See 1 more Smart Citation
“…Previous electrophysiological studies have emphasized the role of NA in the modulation of cortical glutamatergic neurotransmission (Nowicky et al, 1992, Dinh et al, 2009, the latter being the main determinant for the coupling between increased cortical activity and hemodynamic alterations (Attwell and Iadecola, 2002). This is consistent with the numerous c-Fos-positive pyramidal-shaped cells found in our study (not quantified) and, to a lesser extent, COX-2-immunopositive pyramids (ϳ20%).…”
Section: Mediators Of the Hemodynamic Responses To Lc Stimulation Glusupporting
confidence: 92%
“…In contrast, no significant CBF changes were observed with the selective COX-1 inhibitor SC-560 [5-(4-chlorophenyl)-1-(4-methoxyphenyl)-3-trifluoromethyl pyrazole] (2.7 Ϯ 2.2%) (Fig. 5C), as found after sensory or basal forebrain stimulation (Niwa et al, 2000;Lecrux et al, 2011Lecrux et al, , 2012.…”
Section: Mediators Of the Hemodynamic Responses To Lc Stimulation Glumentioning
confidence: 93%
“…In addition to the excitatory inputs, inhibitory inputs to excitatory neurons came largely from the same cortical layer (Katzel et al 2011). Thus the layer-specific modulation of inhibitory transmission by 5-HT in the present study and by norepinephrine (Salgado et al 2011) might be an important factor in pathway-specific information processing. …”
Section: Variable Effects Of 5-ht In the Cortexsupporting
confidence: 47%
“…Layer-specific cholinergic (Cho et al 2008;Gil et al 1997) and adrenergic (Salgado et al 2011) modulation has been reported in layer 2/3 pyramidal neurons, which might be important in the inputspecific modulation of cortical circuits. Thus we investigated the subcellular domain dependence of 5-HT facilitation on IPSC.…”
Section: -Ht 2 Receptor-dependent Facilitation Of Ipscmentioning
confidence: 99%
“…NA excites GABAergic interneurons (McCormick 1992a;Kawaguchi and Shindou 1998) and indirectly inhibits principal neuron activity in different CNS areas (Segal et al 1991). On the other hand, NA can increase GABA A IPSCs of interneurons such as, cerebellar stellate cells (Kondo and Marty 1997), frontal cortex (Kawaguchi and Shindou 1998), cerebellum and have opposite effects in GABAergic neurons of different layers of sensory cortices depending on the type of NAR activated (Salgado et al 2011).…”
Section: Nars-egaba a Rs Interactionmentioning
confidence: 99%